2018
DOI: 10.1364/oe.26.013229
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behavior of nonlinear refractive indexes of CO2 and Xe in supercritical states

Abstract: Direct measurement of pressure dependent nonlinear refractive index of CO and Xe in subcritical and supercritical states are reported. In the vicinity of the ridge (or the Widom line), corresponding to the maximum density fluctuations, the nonlinear refractive index reaches a maximum value (up to 4.8*10m/W in CO and 3.5*10m/W in Xe). Anomalous behavior of the nonlinear refractive index in the vicinity of a ridge is caused by the cluster formation. That corresponds to the results of our theoretical assumption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
21
0
3
Order By: Relevance
“…However, both these approaches have fundamental disadvantages, since anharmonicity effects are taken into account phenomenologically. Recently, excitation spectra in fluids have become of great interest in context of studies concerning the thermodynamics and collective dynamics of fluids 8,26,3262 , and, in particular, crossover from fluid- to gas-like collective dynamics (Frenkel line) 8,32,3441,47,48,5053,56,58 and in the framework of inelastic X-ray or neutron scattering experiments 6376 . Note that these experiments have already revealed a problem of mixing of longitudinal and transverse modes, which plays an important role in a proper analysis of excitation spectra as will be shown below.…”
Section: Introductionmentioning
confidence: 99%
“…However, both these approaches have fundamental disadvantages, since anharmonicity effects are taken into account phenomenologically. Recently, excitation spectra in fluids have become of great interest in context of studies concerning the thermodynamics and collective dynamics of fluids 8,26,3262 , and, in particular, crossover from fluid- to gas-like collective dynamics (Frenkel line) 8,32,3441,47,48,5053,56,58 and in the framework of inelastic X-ray or neutron scattering experiments 6376 . Note that these experiments have already revealed a problem of mixing of longitudinal and transverse modes, which plays an important role in a proper analysis of excitation spectra as will be shown below.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, to identify the current state of matter, it is especially important to have a robust and simple diagnostic tool. The clustering of molecules that occurs in supercritical fluid leads to the modification in the molecular refraction, an increase of the nonlinear refractive index [18] and the offset of the rotational-vibrational transitions [19]. Specific modifications in the SCF microstructure can be detected by optical techniques such as Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The optical diagnostics is not limited by spectroscopic methods [24]. We recently demonstrated that by determining the linear and nonlinear refractive indices, the relative concentration of clusters and the average number of molecules in a cluster can be estimated [18]. Moreover, the nonlinear refractive index measurements are one of the most sensitive approaches due to nonlinear (for instance, n 2 has a quadratic dependence on the cluster concentration) processes [25].…”
Section: Introductionmentioning
confidence: 99%
“…The entrance and exit windows of the cuvette were made of 10 mm thick sapphire and had an aperture diameter of 8 mm. The cuvettes, which were fabricated specially for our experiments, are described in details in our earlier publication [22]. Carbon dioxide with a purity of 99.9% and atmospheric air with humidity less than 10% were used as media for THz generation.…”
Section: Methodsmentioning
confidence: 99%